Assessing the effectiveness of 30% sodium chloride aqueous solution for the preservation of fixed anatomical specimens: a 5-year follow-up study - Oliveira, Fabricio Singaretti de [UNESP] (Wiley-Blackwell, 2014)
Anatomical specimens used in human or veterinary anatomy laboratories are usually prepared with formaldehyde (a cancerous and teratogenic substance), glycerin (an expensive and viscous fluid), or ethanol (which is flammable). This research aimed to verify the viability of an aqueous 30% sodium chloride solution for preservation of anatomical specimens previously fixed with formaldehyde. Anatomical specimens of ruminant, carnivorous, equine, swine and birds were used. All were previously fixed with an aqueous 20% formaldehyde solution and held for 7days in a 10% aqueous solution of the same active ingredient. During the first phase of the experiment, small specimens of animal tissue previously fixed in formaldehyde were distributed in vials with different concentrations of formaldehyde, with or without 30% sodium chloride solution, a group containing only 30% sodium chloride, and a control group containing only water. During this phase, no contamination was observed in any specimen containing 30% sodium chloride solution, whether alone or in combination with different concentrations of formaldehyde. In the second phase of the experiment, the 30% sodium chloride solution, found to be optimal in the first phase of the experiment, was tested for its long-term preservation properties. For a period of 5years, the preserved specimens were evaluated three times a week for visual contamination, odors, and changes in color and texture. There was no visual contamination or decay found in any specimen. Furthermore, no strange odors, or changes in color or softness were noted. The 30% sodium chloride solution was determined to be effective in the preservation of anatomic specimens previously fixed in formaldehyde.
Keywords: Anatomy; class; Preservation